Method for removing polymorphic inorganic phosphorus

By using one-step coupling catalytic oxidation and adsorption method of using biomass-modified iron-based organic frame composite materials and oxidizing agents in electroplating wastewater, the problem of removing multi-form inorganic phosphorus in electroplating wastewater is solved, and the removal effect is achieved with high efficiency and low cost.

CN119528319AActive Publication Date: 2025-02-28JIANGSU PROVINCIAL ACAD OF ENVIRONMENTAL SCI
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411705095.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove multiple forms of inorganic phosphorus, especially phosphites in electroplating wastewater, and the traditional methods are complex and costly, have low adsorption efficiency, and are prone to loss of materials during continuous operation.

Method used

The biomass-modified iron-based organic frame composite material and oxidant are used to add it to the electroplating wastewater, and the multi-form inorganic phosphorus is removed by coupling catalytic oxidation and adsorption in one step. The material is prepared by hydrothermal reaction and calcination, and has high adsorption efficiency and stability.

Benefits of technology

Highly efficient adsorption of phosphate, phosphite and nickel complex phosphite is achieved, with the maximum adsorption amount reaching 2.26mmol/g, 1.89mmol/g and 2.77mmol/g respectively, and the material loss does not exceed 3%. It has a wide pH range and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528319A_ABST
    Figure CN119528319A_ABST
Patent Text Reader

Abstract

The invention discloses a method for removing polymorphic inorganic phosphorus, and belongs to the technical field of environmental material preparation and application. The method comprises the following steps: adding a biomass-based modified iron-based organic framework composite material and an oxidizing agent into the nickel-containing electroplating wastewater, oscillating and adsorbing at normal temperature, and removing polymorphic inorganic phosphorus in the nickel-containing electroplating wastewater; wherein the polymorphic inorganic phosphorus comprises phosphate, phosphite and nickel complex phosphite. The biomass-based modified iron-based organic framework composite material prepared by the invention can realize complex breaking adsorption of a heavy metal-phosphorous acid complex, oxidative adsorption of phosphite and adsorption of orthophosphate in electroplating wastewater in one step, and has the maximum adsorption capacities of 2.26 mmol / g, 1.89 mmol / g and 2.77 mmol / g on phosphate, phosphite and nickel complex phosphite respectively; in practical application, the loss amount does not exceed 3%, and the applicable pH range is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental material preparation and application, and particularly relates to a method for removing polymorphic inorganic phosphorus. Background Art

[0002] Electroplating is an essential basic industry for human industry and life, but due to the large amount of phosphorus-containing polluted wastewater discharged during the process, the electroplating industry has become one of the most dangerous chemical-intensive industries in the world. A variety of wastewater containing phosphorus is used in the production process. Phosphorus is one of the main elements that cause eutrophication of water bodies. It can accelerate the growth of phytoplankton, lead to oxygen depletion, and the death of fish and aquatic organisms. Phosphite (P(III)) is an important component of total dissolved phosphorus (TP) and an emerging eutrophication pollutant that can be converted into phosphate (P(V)) in the biogeochemical phosphorus cycle that occurs naturally in aquatic environments. The accumulation of P(III) in electroplating wastewater comes from phosphorus-containing agents such as phosphoric acid, chelating agents, and reducing agents.

[0003] Nowadays, the removal methods of P(V) have been widely explored, including ion exchange, membrane separation, adsorption and other processes. Compared with other methods, the adsorption method has lower preparation cost and fewer steps. It is suitable for enriching and recovering low-concentration phosphorus using solid functional groups, and has the advantages of simplicity, cheapness and low carbon. However, since P(III) is more easily complexed with heavy metal ions in electroplating wastewater than P(V), common P(V) removal technology cannot be directly applied to P(III). The main method is to oxidize P(III) to P(V) and break the complex system through a two-step removal strategy, and then remove P(V) by precipitation or biological treatment. However, the two-step method is complicated and costly, and precipitation or biological treatment often cannot reduce the total phosphorus concentration to the discharge standard. In recent years, one-step methods such as electro-induced oxidation precipitation, simultaneous oxidation, and filtration have been widely used. Therefore, one-step coupling oxidation and adsorption can promote the entire P(III) removal process and effectively remove P(III) from water.

[0004] Domestic and foreign literature studies have shown that iron-based organic frameworks are a new type of porous coordination polymer material assembled by coordination between iron and organic ligands. It has a unique structure, large specific surface area, uniform, controllable and diverse pore structure, and is widely used in the field of adsorption. It has shown strong ability to absorb phosphorus and resist interference. Modified MOF is conducive to the optimization of its crystal structure and the improvement of porosity. These modification methods usually result in MOFs with unique structures and properties, which ultimately facilitate their adsorption capacity for ions in water. At present, modified MOFs generally have problems such as high cost and energy consumption and low adsorption efficiency. Graphene oxide is widely used to modify the stability and optical properties of MOFs, but it blocks large organic molecules and the size of the electrostatic attraction generated is too small to provide significant selective adsorption. Nitrogen-doped Fe-based MOFs can be used to activate persulfate to further adsorb pollutants, but due to the uneven mixing of raw materials, only nitrogen atoms can be directly incorporated into the carbon framework, and iron is easily aggregated during the carbonization process, resulting in incomplete exposure of active sites and metal leaching, thereby impairing catalytic activity.

[0005] Furthermore, despite good performance in phosphorus uptake, the use of fine particles in wastewater treatment may result in loss of the element and poor recovery and reuse after treatment, leading to higher operating costs. Therefore, it is very important to find a suitable matrix to retain the adsorbent to facilitate the recycling and recovery of the spent adsorbent.

[0006] The Chinese patent number CN114621457A discloses a modified iron-based metal organic framework material and its preparation method and use. FeCl3·6H2O, Ni(NO3)2·6H2O and reagent A are dissolved in N,N-dimethylformamide solution (reagent A is a mixture of terephthalic acid or 2-aminoterephthalic acid and para-mercaptoterephthalic acid), then NaOH solution is added, stirred evenly and transferred to a high-pressure reactor. The pressure value in the high-pressure reactor is 0.2-0.4MPa, and the reaction is carried out at 80-150°C for 15-24h, and then cooled and centrifuged, washed with N,N-dimethylformamide solution, and finally dried at 70-75°C for 15-24h to obtain a modified iron-based metal organic framework material. The patent shows that modifying the organic framework can improve the material's reactivity under visible light, but the material preparation cycle is long, and higher costs are required to achieve better results.

[0007] The Chinese patent number CN117866222A discloses a modified iron-copper bimetallic organic framework material and its preparation method and use: FeCl3·6H2O, Cu(NO3)2·3H2O, and 1,4-naphthalene dicarboxylic acid are dissolved in N,N-dimethylformamide, and NaOH dissolved in ultrapure water is added. After fully mixing, the mixture is reacted at 0.2-0.4Mpa and 80-180°C for 10-20h. After the reaction is completed, the mixture is washed and centrifuged with N,N-dimethylformamide for multiple times, and then reacted at 50-100°C for 15-20h. Finally, the modified iron-copper bimetallic organic framework material Fe-Cu-T100 is obtained by grinding for visible light photocatalytic reduction of CO2. The successful preparation of this material shows that modification of organic framework materials can improve catalytic performance, but this material is only used in the field of photocatalysis and fails to demonstrate its potential in adsorption.

[0008] Chinese patent number CN202210404779.8 discloses a preparation method and application of MIL-100 (Fe) / cellulose porous composite beads. The iron-based organic framework is added to the cellulose solution, stirred evenly, and then added to the metal ion solution for immersion to obtain a composite bead hydrogel, which has the advantages of good mechanical properties, high porosity, and high adsorption efficiency. However, the preparation process does not accurately control whether the iron-based organic framework has a leakage risk.

[0009] Through the search, no relevant patents and public documents for realizing the adsorption of polymorphic inorganic phosphorus in electroplating wastewater in the form of biomass-modified iron-based organic framework composite materials have been found. Therefore, it is urgent to develop a method for effectively improving the adsorption efficiency of polymorphic inorganic phosphorus, while maintaining a high adsorption amount, loading the biomass base to reduce the loss of MOF in continuous operation, and effectively removing polymorphic inorganic phosphorus from electroplating wastewater. Compared with the patent (CN118236986A) previously applied by the inventor, the adsorbed pollutants are expanded from a single phosphate to polymorphic inorganic phosphorus, and the scope of application is the removal of polymorphic inorganic phosphorus in nickel-containing electroplating wastewater. Summary of the invention

[0010] In view of the above problems existing in the prior art, the technical problem to be solved by the present invention is to provide a method for removing polymorphic inorganic phosphorus, which adopts a one-step coupling catalytic oxidation and adsorption of inorganic phosphorus, and the method is simple and low-cost.

[0011] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0012] A method for removing polymorphic inorganic phosphorus comprises adding a biomass-based-modified iron-based organic framework composite material and an oxidant into nickel-containing electroplating wastewater, and performing oscillation adsorption at room temperature to remove polymorphic inorganic phosphorus in the nickel-containing electroplating wastewater; wherein the polymorphic inorganic phosphorus comprises phosphate, phosphite, and nickel-complexed phosphite; and the nickel-containing electroplating wastewater contains 0.25 to 4 mmol / L of nickel chloride and phosphite.

[0013] Preferably, the mass ratio of the biomass-based-modified iron-based organic framework composite material to the oxidant is 0.5-1.5:0.04-0.08.

[0014] Preferably, the preparation process of the biomass-based-modified iron-based organic framework composite material is: subjecting the precursor to a hydrothermal reaction and then calcining it to prepare a modified iron-based organic framework Cc-BA-MIL-88 (B), and reacting the modified iron-based organic framework Cc-BA-MIL-88 (B), chitosan, a cross-linking agent and a mixed solution to obtain a biomass-based-modified iron-based organic framework composite material.

[0015] Preferably, the precursor is prepared by uniformly mixing benzoic acid, terephthalic acid, ferric chloride hexahydrate and N,N-dimethylformamide to obtain a precursor.

[0016] Preferably, the mmol / mmol / mmol / mL ratio of benzoic acid, terephthalic acid, ferric chloride hexahydrate and N,N-dimethylformamide is 3.2:12.8:16:100.

[0017] Preferably, the calcination is carried out in a nitrogen atmosphere, the calcination temperature is 400° C., and the calcination time is 4-6 hours.

[0018] Preferably, the oxidant is sodium persulfate.

[0019] A method for preparing a biomass-based-modified iron-based organic framework composite material for the method for removing polymorphic inorganic phosphorus, specifically comprising the following steps:

[0020] 1) Benzoic acid, terephthalic acid, ferric chloride hexahydrate and N,N-dimethylformamide are uniformly mixed to form a precursor, the precursor is subjected to a hydrothermal reaction, centrifuged and then dried to obtain BA-MIL-88 (B);

[0021] 2) calcining the BA-MIL-88 (B) obtained in step 1) to obtain a modified iron-based organic framework Cc-BA-MIL-88 (B);

[0022] 3) adding the modified iron-based organic framework Cc-BA-MIL-88(B), chitosan and a crosslinking agent obtained in step 2) into an acetic acid solution, mixing them evenly, and then heating them in a water bath at 60° C. for crosslinking for 2 h to obtain a mixed material;

[0023] 4) dropping the mixture obtained in step 3) into a mixed solution containing sodium hydroxide, sodium sulfate, anhydrous ethanol and water to obtain a hydrogel; placing the obtained hydrogel in a diluted cross-linking agent to enhance the mechanical strength, washing and drying at room temperature to obtain a biomass-based-modified iron-based organic framework composite material.

[0024] Preferably, the g / g / mL ratio of the modified iron-based organic framework Cc-BA-MIL-88(B), chitosan and cross-linking agent is 1:0.6:0.154.

[0025] Preferably, the cross-linking agent is epichlorohydrin.

[0026] Preferably, in the mixed solution, the g / g / mL / mL ratio of sodium hydroxide, sodium sulfate, anhydrous ethanol and water is 16:12:2:300.

[0027] The method for preparing the biomass-based-modified iron-based organic framework composite material prepares the biomass-based-modified iron-based organic framework composite material.

[0028] The biomass-based-modified iron-based organic framework composite material is used as an adsorbent in the adsorption of polymorphic inorganic phosphorus pollutants in nickel-containing electroplating wastewater.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) In the method for removing polymorphic inorganic phosphorus provided by the present invention, the prepared biomass-based-modified iron-based organic framework composite material can be applied to the removal of polymorphic inorganic phosphorus in nickel-containing electroplating wastewater, and the maximum adsorption capacity of phosphate, phosphite, and nickel-complexed phosphite can reach 2.26mmol / g, 1.89mmol / g, and 2.77mmol / g, respectively;

[0031] (2) The biomass-based-modified iron-based organic framework composite material prepared by the present invention has the best effect of enhancing the adsorption and removal capacity of inorganic phosphorus when the molar ratio of benzoic acid to terephthalic acid is 2:8, and the adsorption effect of phosphate, phosphite, and phosphite containing nickel ions is not less than 1.5 mmol / g;

[0032] (3) The loss of the biomass-based-modified iron-based organic framework composite material prepared by the present invention does not exceed 3% in practical applications, indicating that the biomass-based material chitosan effectively reduces the loss of the material;

[0033] (4) Compared with the traditional Fenton method and biological phosphorus removal, the Cc-BA-MIL-88(B)@Cs prepared by the present invention has a wider pH range for removing inorganic phosphorus from nickel-containing water bodies by adsorption, and has a good removal effect at a pH of 4-10;

[0034] (5) The method for removing polymorphic inorganic phosphorus of the present invention is simple and low-cost. It also has a good removal effect in low-concentration electroplating nickel-containing inorganic phosphorus wastewater by one-step coupling catalytic oxidation and adsorption of inorganic phosphorus through the prepared biomass-based-modified iron-based organic framework composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 SEM images of Cc-BA-MIL-88(B)@Cs(a, d, g), BA-MIL-88(B)@Cs(b, e, h), and MIL-88(B)@Cs(c, f, i);

[0036] Figure 2 EPR spectra of Cc-BA-MIL-88(B)@Cs and MIL-88(B)@Cs;

[0037] Figure 3 The adsorption effect of Cc-BA-MIL-88(B)@Cs, BA-MIL-88(B)@Cs, and MIL-88(B)@Cs on 1 mmol / L inorganic phosphorus in various forms;

[0038] Figure 4 This is the adsorption effect diagram of Cc-BA-MIL-88(B)@Cs on various forms of inorganic phosphorus at different benzoic acid ratios;

[0039] Figure 5 This is the removal effect diagram of Cc-BA-MIL-88(B)@Cs on phosphite of different concentrations;

[0040] Figure 6 This is the adsorption effect diagram of Cc-BA-MIL-88(B)@Cs on phosphite of different concentrations at different temperatures;

[0041] Figure 7 This is the proportion of each effect in the process of Cc-BA-MIL-88(B)@Cs adsorbing nickel-containing phosphite solution;

[0042] Figure 8 The adsorption effect of Cc-BA-MIL-88(B)@Cs on inorganic phosphorus and the loss of iron ions under different pH conditions are compared with the traditional method;

[0043] Fig. 9This is a diagram showing the effect of Cc-BA-MIL-88(B)@Cs in adsorbing inorganic phosphorus in nickel-containing electroplating wastewater. DETAILED DESCRIPTION

[0044] The present invention will be further illustrated below in conjunction with specific examples. The examples are implemented under the premise of the technical solution of the present invention. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. In the following examples, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art. In the examples, those without specifying specific conditions are carried out according to conventional conditions or the conditions recommended by the manufacturer. Those without specifying the manufacturer for reagents used or instruments are conventional products that can be obtained by commercial purchase.

[0045] The performance testing method adopted by the present invention is as follows:

[0046] (1) The test method for the content of inorganic phosphorus in various forms is: ammonium molybdate spectrophotometry (GB / T11893-1989).

[0047] (2) The iron ion content was measured by flame atomic absorption spectrophotometry (GB / T11911-1989).

[0048] Example 1

[0049] A method for preparing a biomass-based-modified iron-based organic framework composite material for removing polymorphic inorganic phosphorus comprises the following steps:

[0050] 1) 3.2 mmol benzoic acid, 12.8 mmol terephthalic acid and 16 mmol ferric chloride hexahydrate were added into 100 mL N,N-dimethylformamide and completely dissolved, kept at 150°C in an autoclave for 12 h, washed with deionized water and methanol alternately for several times, and dried to obtain 1.88 g BA-MIL-88 (B);

[0051] 2) 1.5 g of BA-MIL-88 (B) prepared in step 1) was calcined at 400° C. in a nitrogen atmosphere for 4 h to obtain 1.35 g of a modified iron-based organic framework Cc-BA-MIL-88 (B);

[0052] 3) 1.0 g of modified iron-based organic framework Cc-BA-MIL-88(B), 0.6 g of chitosan and 0.154 mL of epichlorohydrin were respectively added to 20 mL of 2% (V / V) acetic acid solution, cross-linked at 60°C for 2 h, and 300 mL of a mixed solution containing 16 g of sodium hydroxide, 12 g of sodium sulfate and 2 mL of anhydrous ethanol was dropped into it with a syringe to fully cross-link to form a hydrogel. The hydrogel was cross-linked in 100 mL of distilled water containing 0.5 mL of epichlorohydrin for 2 h to enhance the mechanical strength. After washing, the hydrogel was dried at room temperature to obtain 12.17 g of biomass-based-modified iron-based organic framework composite material Cc-BA-MIL-88(B)@Cs.

[0053] Comparative Example 1

[0054] 1.0 g MIL-88(B), 0.6 g chitosan and 0.154 mL epichlorohydrin were weighed and added into 20 mL of 2% (V / V) acetic acid solution respectively, and cross-linked at 60°C for 2 h. 300 mL of a mixed solution containing 16 g sodium hydroxide, 12 g sodium sulfate and 2 mL anhydrous ethanol was dropped into the solution with a syringe to fully cross-link and form a hydrogel. The hydrogel was cross-linked in 100 mL distilled water containing 0.5 mL epichlorohydrin for 2 h to enhance the mechanical strength. After washing and drying at room temperature, 12.85 g of material MIL-88(B)@Cs was obtained.

[0055] Comparative Example 2

[0056] 1) 3.2 mmol benzoic acid, 12.8 mmol terephthalic acid and 16 mmol ferric chloride hexahydrate were added to 100 mL N, N-dimethylformamide and completely dissolved, kept at 150 ° C in an autoclave for 12 h, washed with deionized water and methanol alternately for several times, and dried to obtain 1.88 g of material BA-MIL-88 (B);

[0057] 2) 1.0 g of BA-MIL-88 (B) prepared in step 1), 0.6 g of chitosan and 0.154 mL of epichlorohydrin were respectively added to 20 mL of 2% (V / V) acetic acid solution, cross-linked at 60°C for 2 h, and 300 mL of a mixed solution containing 16 g of sodium hydroxide, 12 g of sodium sulfate and 2 mL of anhydrous ethanol was dropped into the solution with a syringe to fully cross-link to form a hydrogel. The hydrogel was cross-linked in 100 mL of distilled water containing 0.5 mL of epichlorohydrin for 2 h to enhance the mechanical strength. After washing, the solution was dried at room temperature to obtain 12.43 g of BA-MIL-88 (B) @ Cs.

[0058] Depend on Figure 1It can be seen that the surface structure of MIL-88(B)@Cs is relatively smooth. After the introduction of defects, the modified iron-based organic framework in Cc-BA-MIL-88(B)@Cs can retain the similar morphology of the iron-based organic framework in MIL-88(B)@Cs, but their surface becomes obviously rough, and the surface roughness gradually increases with the introduction of benzoic acid and the calcination process. These defects are formed during the modification and calcination process, accompanied by the appearance of several uniformly distributed particles.

[0059] Depend on Figure 2 It can be seen that the measurement of vacancy defects of Cc-BA-MIL-88(B)@Cs and MIL-88(B)@Cs proves that the defects appearing after modification are oxygen vacancies. The positively charged oxygen vacancies can promote the adsorption of negatively charged phosphates in phosphates, negatively charged phosphites in phosphites, and negatively charged phosphates in phosphates oxidized from phosphites after the nickel chloride complex phosphites are broken through the electrostatic attraction effect, thereby providing more adsorption sites.

[0060] Comparative Example 3

[0061] 1) When the total amount of benzoic acid and terephthalic acid is 16 mmol, the proportion of benzoic acid is controlled to be 0% to 50%, benzoic acid, terephthalic acid and 16 mmol of ferric chloride hexahydrate are added to 100 mL of N, N-dimethylformamide and completely dissolved, kept at 150° C. for 12 h in an autoclave, washed several times with deionized water and methanol alternately, and dried to obtain 1.72 g to 1.98 g (0% to 50%) of BA-MIL-88 (B);

[0062] 2) 1.5 g of the (0% to 50%) BA-MIL-88 (B) prepared in step 1) was calcined at 400° C. in a nitrogen atmosphere for 4 h to obtain 1.24 g to 1.42 g of modified iron-based organic framework Cc-(0% to 50%) BA-MIL-88 (B);

[0063] 3) 1.0g of the modified iron-based organic framework Cc-(0% to 50%) BA-MIL-88(B) prepared in step 2), 0.6g of chitosan and 0.154mL of epichlorohydrin were added to 20mL of 2% (V / V) acetic acid solution, crosslinked at 60°C for 2h, and a 300mL mixed solution containing 16g of sodium hydroxide, 12g of sodium sulfate and 2mL of anhydrous ethanol was added dropwise with a syringe to fully crosslink to form a hydrogel, and crosslinked in 100mL of distilled water containing 0.5mL of epichlorohydrin for 2h to enhance the mechanical strength, washed and dried at room temperature to obtain 11.13 to 12.82g of biomass-based-modified iron-based organic framework composite material Cc-(0% to 50%) BA-MIL-88(B)@Cs. Among them, Cc-(20%) BA-MIL-88(B)@Cs is Cc-BA-MIL-88(B)@Cs prepared in Example 1.

[0064] Example 2

[0065] 50 mL of a mixed solution containing phosphate, phosphite, and nickel chloride complex phosphite was prepared respectively, wherein the concentrations of phosphate, phosphite, and nickel chloride complex phosphite were all 1 mmol / L, and the pH value was adjusted to 8.0. Then, 0.08 g of an oxidant, sodium persulfate, and 1.5 g of an adsorbent to be tested were added thereto respectively, and the mixture was shaken at room temperature of 25°C for 24 hours. The inorganic phosphorus content in the solution was determined by ammonium molybdate spectrophotometry (GB / T 11893-1989). The adsorption amounts of phosphate, phosphite, and nickel chloride complex phosphite in the solution by Cc-BA-MIL-88(B)@Cs prepared in Example 1, MIL-88(B)@Cs prepared in Comparative Example 1, and BA-MIL-88(B)@Cs prepared in Comparative Example 2 were as follows: Figure 3 And as shown in Table 1.

[0066] Table 1 Adsorption results of solutions containing phosphate, phosphite, and nickel chloride complex phosphite

[0067]

[0068] From Table 1 and Figure 3It can be seen that the adsorption capacity of Cc-BA-MIL-88(B)@Cs prepared in Example 1 for 1mmol / L phosphate is 0.68mmol / g, which is higher than the adsorption capacity of MIL-88(B)@Cs prepared in Comparative Example 1 for 1mmol / L phosphate (0.25mmol / g) and the adsorption capacity of BA-MIL-88(B)@Cs prepared in Comparative Example 2 for 1mmol / L phosphate (0.34mmol / g); the adsorption capacity of Cc-BA-MIL-88(B)@Cs prepared in Example 1 for 1mmol / L phosphite is 0.56mmol / g, which is higher than the adsorption capacity of MIL-88(B)@Cs prepared in Comparative Example 1 for 1mmol / L phosphite adsorption capacity (0.21mmol / g) and the BA-MIL-88(B)@Cs prepared in Comparative Example 2 adsorbs 1mmol / L phosphite (0.28mmol / g); the adsorption capacity of Cc-BA-MIL-88(B)@Cs for 1mmol / L nickel chloride complex phosphite is 1.02mmol / g, which is higher than the adsorption capacity of MIL-88(B)@Cs prepared in Comparative Example 1 for 1mmol / L nickel chloride complex phosphite (0.31mmol / g) and the adsorption capacity of BA-MIL-88(B)@Cs prepared in Comparative Example 2 for 1mmol / L nickel chloride complex phosphite (0.51mmol / g). The results show that benzoic acid modification effectively improves the adsorption capacity of the material for phosphate and phosphite, calcination increases the catalytic performance of the material, and accelerates the decomposition of nickel chloride complex phosphite and the oxidation of phosphite. Figure 1 and Figure 2 As shown in the results, the benzoic acid modification and calcination process endowed the iron-based organic framework with many oxygen vacancies and active sites, which was beneficial to improve the adsorption performance of the material for phosphite. During the adsorption process, the possible mechanism mainly depends on the electrostatic attraction and the complexation between the oxygen vacancies from the Fe-O bonds.

[0069] Example 3

[0070] 50 mL of solutions containing phosphate, phosphite, and nickel chloride complex phosphite were prepared respectively, wherein the concentrations of phosphate, phosphite, and nickel chloride complex phosphite were all 1 mmol / L, and the pH value was adjusted to 8.0. 0.08 g of oxidant sodium persulfate and 1.5 g of Cc-BA-MIL-88(B)@Cs prepared in Example 1 and Cc-(0% to 50%) BA-MIL-88(B)@Cs prepared in Comparative Example 3 were added respectively, and the mixture was shaken at room temperature of 25°C for 24 h. The inorganic phosphorus concentration of the solution was determined by ammonium molybdate spectrophotometry (GB / T 11893-1989). The maximum adsorption capacity of Cc-BA-MIL-88(B)@Cs prepared in Example 1 and Cc-(0% to 50%) BA-MIL-88(B)@Cs prepared in Comparative Example 3 for phosphate, phosphite, and nickel chloride complex phosphite in the solution was as follows: Figure 4 And as shown in Table 2.

[0071] Table 2 Adsorption results of solutions containing phosphate, phosphite, and nickel chloride complex phosphite

[0072]

[0073] From Table 2 and Figure 4 It can be seen that when the proportion of benzoic acid is 20%, that is, the preparation conditions of Example 1, the prepared biomass-based-modified iron-based organic framework composite material has the best adsorption effect on phosphate, phosphite, and phosphite containing nickel chloride, proving that the optimal ratio of benzoic acid to terephthalic acid in Example 1 is 2:8.

[0074] Example 4

[0075] 50 mL of solutions with nickel chloride and phosphite concentrations of 0.25, 0.5, 1, 2 and 4 mmol / L were prepared respectively, and the pH value was adjusted to 8.0. 0.04 g of oxidant sodium persulfate and 0.5 g of Cc-BA-MIL-88(B)@Cs prepared in Example 1 were added respectively. The mixture was shaken at 15° C., 25° C. and 35° C. for 24 h, and the phosphite concentration of the solution was determined by ammonium molybdate spectrophotometry (GB / T 11893-1989). The results are shown in Tables 3, 4, and 5. Figure 5 and Figure 6 shown.

[0076] Table 3 Phosphite adsorption by Cc-BA-MIL-88(B)@Cs at different phosphorous acid concentrations and temperatures

[0077]

[0078]

[0079] Table 4 Fitting parameters of adsorption isotherms of phosphite by Cc-BA-MIL-88(B)@Cs at different temperatures

[0080]

[0081] From Table 3 and Figure 6 It can be seen that the maximum adsorption capacity of phosphite by Cc-BA-MIL-88(B)@Cs prepared in Example 1 can reach 2.77 mmol / g at room temperature (25°C); during the adsorption of phosphite, the adsorption of phosphite increases with the increase of temperature, indicating that the adsorption of phosphite by Cc-BA-MIL-88(B)@Cs is an endothermic process, and nickel chloride promotes the adsorption of phosphite after breaking the complex.

[0082] It can be seen from Table 4 that the adsorption process of phosphite by the biomass-based-modified iron-based organic framework composite material Cc-BA-MIL-88(B)@Cs is more consistent with the Friedrich isotherm, which indicates that Cc-BA-MIL-88(B)@Cs performs multilayer adsorption on the heterogeneous surface to remove phosphite.

[0083] Example 5

[0084] 50 mL of a solution containing 1 mmol / L phosphite was prepared, and 0.5 g of Cc-BA-MIL-88(B)@Cs prepared in Example 1 was added in the presence or absence of 0.04 g of an oxidant sodium persulfate and in the presence or absence of 1 mmol / L nickel chloride, respectively. The mixture was shaken at room temperature 25°C for 24 h, and the phosphite concentration of the solution was determined by ammonium molybdate spectrophotometry (GB / T11893-1989).

[0085] Table 5 Results of adsorption of 1mmol / L phosphite with and without oxidant and nickel chloride

[0086]

[0087] From Table 5 and Figure 7 It can be seen that in the process of adsorbing nickel chloride complexed phosphite solution, the biomass-based-modified iron-based organic framework composite material Cc-BA-MIL-88(B)@Cs prepared in Example 1 has three processes: direct adsorption of phosphite, oxidation of phosphite to phosphate and adsorption, and nickel-promoted adsorption. At the maximum adsorption amount of 2.77 mmol / g, the direct adsorption of phosphite is 0.45 mmol / g, the oxidation of phosphite to phosphate and adsorption is 1.44 mmol / g, and the nickel-promoted adsorption is 0.88 mmol / g. The three effects account for 16%:52%:32%.

[0088] Example 6

[0089] Prepare 50mL of solutions containing phosphate, phosphite, and nickel chloride complex phosphite, wherein the concentrations of phosphate, phosphite, and nickel chloride complex phosphite are all 1mmol / L, and adjust the pH values ​​to 4, 5, 6, 7, 8, 9, and 10, respectively. In the first solution, Cc-BA-MIL-88(B)@Cs prepared in Example 1 was used, and 0.08g of oxidant sodium persulfate and 1.0g of Cc-BA-MIL-88(B)@Cs prepared in Example 1 were added, respectively, and the mixture was shaken at 25°C for 24h. The second solution was prepared using the Fenton method, and 5mL of 27.5% hydrogen peroxide and 0.02g of ferrous sulfate were added, respectively, and the mixture was shaken at 25°C for 24h. The third solution was prepared using the biological method, and 1.0g of polyphosphate bacteria was added, respectively, and the mixture was shaken at 25°C for 24h. The phosphite concentration of the solution was determined by ammonium molybdate spectrophotometry (GB / T 11893-1989). The iron ion concentration of the first solution was determined by flame atomic absorption spectrophotometry (GB / T 11911-1989). The results are shown in Table 6 and Figure 8 shown.

[0090] Table 6 Comparison of the adsorption effect of Cc-BA-MIL-88(B)@Cs on inorganic phosphorus and iron ion loss under different pH conditions and the traditional method

[0091]

[0092]

[0093] From Table 6 and Figure 8 It can be seen that Cc-BA-MIL-88(B)@Cs has a good adsorption effect in the pH range of 4-10, and the loss of Cc-BA-MIL-88(B)@Cs does not exceed 3%. The results show that the biomass-based material chitosan effectively reduces the loss of materials. Compared with the acidic conditions of the traditional Fenton method and the moderately alkaline conditions of the biological method, the applicable pH for Cc-BA-MIL-88(B)@Cs to adsorb and remove inorganic phosphorus is 4-10, which is a wider range.

[0094] Example 7

[0095] Adsorption of inorganic phosphorus in actual nickel-containing electroplating wastewater. Prepare 6 groups of 50 mL nickel-containing electroplating wastewater (the components are shown in Table 7), add 0.04 g of oxidant sodium persulfate and 0.5 g of Cc-BA-MIL-88(B)@Cs prepared in Example 1, shake at room temperature 25°C for 24 h, and use ammonium molybdate spectrophotometry (GB / T11893-1989) to determine the phosphite concentration of the solution. The results are shown in Table 8 and Fig. 9 shown.

[0096] Table 7 Main components of nickel-containing electroplating wastewater

[0097] Ingredients or properties content Phosphate 0.34mg / L Phosphite 0.6mg / L Nickel Ion 0.31mg / L pH 7.27 temperature 23.4℃ Conductivity 177μs / cm COD 240mg / L Sulfate ion 0.14mg / L

[0098] Table 8 Results of actual adsorption of inorganic phosphorus in nickel-containing electroplating wastewater by Cc-BA-MIL-88(B)@Cs

[0099]

[0100]

[0101] From Table 8 and Fig. 9 It can be seen that the average removal rate of Cc-BA-MIL-88(B)@Cs for nickel-containing electroplating wastewater with an initial phosphite concentration of 0.94 mg / L is over 90%, indicating that Cc-BA-MIL-88(B)@Cs has excellent ability to adsorb various forms of inorganic phosphorus in actual electroplating wastewater.

[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for removing polymorphic inorganic phosphorus, characterized in that: Biomass-based-modified iron-based organic framework composite materials and oxidants are added to nickel-containing electroplating wastewater, and oscillation adsorption is performed at room temperature to remove polymorphic inorganic phosphorus in the nickel-containing electroplating wastewater; wherein the polymorphic inorganic phosphorus includes phosphate, phosphite, and nickel-complexed phosphite; the nickel-containing electroplating wastewater contains 0.25 to 4 mmol / L of nickel ions and phosphites.

2. The method for removing polymorphic inorganic phosphorus according to claim 1, characterized in that: The mass ratio of the biomass-based-modified iron-based organic framework composite material to the oxidant is 0.5-1.5:0.04-0.

08.

3. The method for removing polymorphic inorganic phosphorus according to claim 1, characterized in that: The preparation process of the biomass-based-modified iron-based organic framework composite material is as follows: a precursor is subjected to a hydrothermal reaction and then calcined to prepare a modified iron-based organic framework Cc-BA-MIL-88 (B); the modified iron-based organic framework Cc-BA-MIL-88 (B), chitosan, a cross-linking agent and a mixed solution are reacted to obtain a biomass-based-modified iron-based organic framework composite material.

4. The method for removing polymorphic inorganic phosphorus according to claim 3, characterized in that: The preparation process of the precursor is: benzoic acid, terephthalic acid, ferric chloride hexahydrate and N,N-dimethylformamide are mixed evenly to obtain the precursor.

5. The method for removing polymorphic inorganic phosphorus according to claim 4, characterized in that: The mmol / mmol / mmol / mL ratio of benzoic acid, terephthalic acid, ferric chloride hexahydrate and N,N-dimethylformamide is 3.2:12.8:16:

100.

6. The method for removing polymorphic inorganic phosphorus according to claim 3, characterized in that: The calcination is carried out in a nitrogen atmosphere at a temperature of 400° C. for a time of 4-6 hours.

7. The method for removing polymorphic inorganic phosphorus according to claim 1, characterized in that: The oxidant is sodium persulfate.

8. A method for preparing a biomass-based-modified iron-based organic framework composite material for use in the method for removing polymorphic inorganic phosphorus according to any one of claims 1 to 7, characterized in that: The specific steps include: 1) Benzoic acid, terephthalic acid, ferric chloride hexahydrate and N,N-dimethylformamide are uniformly mixed to form a precursor, the precursor is subjected to a hydrothermal reaction, centrifuged and then dried to obtain BA-MIL-88 (B); 2) calcining the BA-MIL-88 (B) obtained in step 1) to obtain a modified iron-based organic framework Cc-BA-MIL-88 (B); 3) adding the modified iron-based organic framework Cc-BA-MIL-88(B), chitosan and a crosslinking agent obtained in step 2) into an acetic acid solution, mixing them evenly, and then heating them in a water bath at 60° C. for crosslinking for 2 h to obtain a mixed material; 4) dropping the mixture obtained in step 3) into a mixed solution containing sodium hydroxide, sodium sulfate, anhydrous ethanol and water to obtain a hydrogel; placing the obtained hydrogel in a diluted cross-linking agent to enhance the mechanical strength, washing and drying at room temperature to obtain a biomass-based-modified iron-based organic framework composite material.

9. The method for preparing the biomass-based-modified iron-based organic framework composite material according to claim 8, wherein the biomass-based-modified iron-based organic framework composite material is prepared.

10. Use of the biomass-based-modified iron-based organic framework composite material according to claim 9 as an adsorbent in the adsorption of polymorphic inorganic phosphorus pollutants in nickel-containing electroplating wastewater.

Citation Information

Patent Citations

  • Modified iron-based metal organic framework material as well as preparation method and application thereof

    CN114621457A

  • A method for preparing and applying MIL-100(Fe) / cellulose porous composite microspheres

    CN114672064B

  • Modified iron-copper-based bimetal organic framework material as well as preparation method and application thereof

    CN117866222A

  • Functionalized iron metal organic frameworks and preparation method thereof

    CN108147959A

  • Controllable preparation method of MIL material and application of MIL material in separation and enrichment of polyhydric alcohols

    CN114618441A